Клініко-епідеміологічні паралелі: охоплення вакцинацією проти "Поліо" - випадки гострих в'ялих паралічів у дітей - Усачова, Олена Віталіївна; Сіліна, Єлизавета Андріївна; Пахольчук, Тетяна Миколаївна; Конакова, Ольга Володимирівна; Дралова, Олександра Анатоліївна; Ніколаєва, Світлана Леонідівна; Пухір, В. П.; Фірюліна, О. М.; Зеленухіна, Є. В.; Usachova, O. V.; Silina, Ye. A.; Pakholchuk, T. M.; et al. (My University, 2018)
WHO declares Ukraine a high*risk country for wild poliovirus circulation in the event of its introduction from polio*endemic countries. Objective: to determine the place of acute flaccid paralysis (AFP) surveillance in children of Zaporizhzhia Oblast and laboratory control over the poliovirus circulation, comparing them with the activity of population immunity. Material and methods. Intensity of vaccine-induced immunity against poliomyelitis in 1385 serum samples from children during the period of 2012–2016 was estimated. The medical documentation of 46 paediatric patients with AFP under 15 years old was analysed. Results. From 2.5 per cent to 25.2 per cent of children of all ages during the last 5 years were nonimmune to at least one type of poliovirus, especially to type 3. From the environmental samples, only vaccine*derived polioviruses have been isolated in the last five years. There were 44 seropositive out of 46 children with AFP. The manifestations of AFP included limitation of limb movements, decreased muscle tone, diminished deep tendon reflexes, positive tension syndrome and severe muscle tenderness on palpation. Wild poliovirus has not been isolated in any case. Conclusions. A gradual decrease in the intensity of immunity against polio was noted that was associated with the worsening vaccination coverage of the child population. During the period of 2014–2016 an annual increase in the number of registered AFP cases of non*poliomyelitis aetiology is recorded, which coincides with the round nationwide vaccination campaign with live attenuated polio vaccines and an increase in the vaccine*derived poliovirus isolation from the environment.
Clinical and epidemiological parallels: vaccination coverage against "Polio" - cases of acute flaccid paralysis